European Training Requirements for the Specialty of Geriatric Medicine - Romero-Ortuno, Roman (UEMS, European Union of Medical Specialists, 2025)
The UEMS (Union Europé enne des Mé decins Spé cialistes, or European Union of Medical Specialists) is a non-governmental organisation representing national associations of medical specialists at the European level. With its current membership of 41 national associations and operating through 43 Specialist Sections and their European Boards, 19 Multidisciplinary Joint Committees and 7 Thematic Federations, the UEMS is committed to promote the free movement of medical specialists across Europe while ensuring the professional consensus on the framework for the highest possible level of their training, which will pave the way to the improvement of quality of care for the benefit of all European citizens and beyond.
PUBLISHED
Keywords: Ageing; Geriatrics; Professional Education; Age-related disability; Third age/ageing